The Activities of the Lithuanian Educational Society Rytas in Vilnius and Vilnius Area (1920–1939) - Ereminas, Gintautas (Genocidas ir rezistencija, 2013)
The subject of the article is Lithuanian education, which was carried out by the Lithuanian educational society Rytas during a politically difficult period for Lithuania. Based on the materials of the Lithuanian educational society Rytas in the Manuscripts Department of the Wroblewski Library of the Lithuanian Academy of Sciences, the aim is to reconstruct the activities of the Society in Vilnius region.